Administración sistémica adjunta de moxifloxacina versus ciprofloxacina más metronidazol en el tratamiento de periodontitis crónica con presencia de bacilos entéricos Gram negativos: II. Analisis multinivel (2012)
ABSTRACT: The site, tooth, and patient levels are involved in the periodontal inflammatory process. The purpose of this study was to compare the effect of site, tooth, and patient-related factors on the success of scaling and root planing combined with systemic administration of moxifloxacin or ciprofloxacin plus metronidazole in the treatment of subjects with chronic periodontitis harboring Gramnegative enteric rods. Methods: seventy-six patients participated in this randomized clinical trial, divided into two groups. The subjects were treated with scaling and root planing plus adjunctive moxifloxacin (moxifloxacin group; n = 38) or scaling and root planing plus adjunctive ciprofloxacin plus metronidazole (ciprofloxacin plus metronidazole group; n = 38). Periodontal and microbiological data were recorded at baseline and at 3 and 6 months after treatment. The relative contribution of patient, tooth and site-associated parameters was evaluated with a hierarchical multilevel model. Results: most of the variance was attributed to site level (73%), followed by tooth level (18.1%) and patient level (8.9%). The multilevel analysis associated probing depth reductions with subject factors (smoking status and treatment), tooth factors (tooth type), and site factors (mesial-distal location). Probing depth reduction was significantly smaller in smokers. Both treatment protocols significantly reduced probing depth. Anterior teeth responded better than posterior teeth. At the site level, greater reductions were observed at interdental sites. The presence of plaque and bleeding on probing at the tooth site level had a significant negative impact on the outcome of chronic periodontitis harboring Gram-negative enteric rods. Conclusions: smoking habits, tooth type, mesial-distal location, plaque and bleeding on probing at site level were significant factors in determining the clinical outcome of scaling and root planing plus adjunctive antibiotic treatment in chronic periodontitis harboring Gram-negative enteric rods.